INNOVATIVE APPROACHES AND FOREIGN EXPERIENCE IN MANAGING EDUCATION QUALITY (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article provides information about the management system in improving the quality of education system in our society, and discusses management strucres and their significance literacy levels, and regionalcharacristics of management strategies in highereducation institutions of developed countries.